Development of a 170Tm source for mercury monitoring studies in humans using XRF. (April 2016) - Timmaraju, K. Phanisree; Fajurally, Bibi Najah; Armstrong, Andrea F.; Chettle, David R.
Abstract: The goals of the present study were to develop a 170 Tm radioisotope and generate a K XRF spectrum of mercury. Thulium foil and thulium oxide powder were both tested for impurities and the latter was found to be a better prospect for further studies. The 170 Tm radioisotope was developed from thulium oxide powder following the method of disolution and absorption. A suitable source holder and collimator were also designed based on Monte Carlo simulations. Using the radioisotope thus developed, a mercury XRF spectrum was successfully generated. Highlights: We tested the purity of thulium samples by XRF and NAA techniques. Developed a procedure to generate Tm-170 isotope out of thulium oxide powder. Designed a collimator and source holder Generated XRF spectrum of mercury using the Tm-170 isotope. Compared the highlights in mercury spectra from Tm-170 and Cd-109 isotopes.